Determination of Mining Risks at Exploitation in Rosia Poieni Open Pit Mine, Romania - Toderas, Mihaela (Techniques and Innovation in Engineering Research Vol. 3, 2022)
The mining sector is an especially important field because it can help a country's economic development by supplying different mineral products that are utilized as raw materials in other sectors of activity. When the depth of a deposit and the geological conditions permit, useful mineral substances are extracted through open-pit mining. The purpose of this paper is to examine the malfunctions that could occur and result in vulnerable incidents, which could have an impact on staff safety and the environment. These malfunctions can have a variety of causes, including internal mining unit malfunctions or natural phenomena. The prospective mining risks that may take place in the Rosia Poieni open pit mine have been identified and evaluated in this study. The guidelines underlying the identification of these risks took into account three main principles: reducing risks for people, making sure their security and at the same time restricting the risks on the property, respectively the financial risk for the mining unit. Recognizing these risks allows for the delimitation of areas that are directly or indirectly exposed to potential risks, as well as the establishment of specific measures for prevention, protection, and security in relation to the activities carried out. Based on the potential mining risks identified, we created a hazard map that can be utilized to develop a risk prevention plan, taking into account the presence of multiple types of risks that may overlap in the same work area of the quarry.